Perbandingan Perlindungan Hukum terhadap Penjiplakan Merek di Indonesia dan Singapura - Masayu Nilam Permata Sari (Jurnal Hukum Lex Generalis, 2025)
an international treaty is an agreement made by two or more countries to regulate their relations in various fields, such as politics, economics, security, or the environment. The relevance of an international treaty lies in its efforts to create cooperation, prevent conflict, and ensure that common interests can be realized fairly. If the agreement focuses on trade, it can open up new market access, increase investment, and strengthen economic relations between the two countries. Defense treaties or security alliances help prevent military threats and create regional stability.This study aims to determine the similarities and differences in legal protection related to trademark plagiarism in Indonesia and Singapore and to identify the factors that cause similarities and differences in the legal systems related to trademark plagiarism in both countries. The findings of this study indicate that Indonesia adheres to the Civil Law system with the principle of first-to-file registration, while Singapore follows the Common Law system with a self-assessment approach. Although both countries have ratified international agreements such as TRIPs, real differences are seen in the way law enforcement and dispute resolution are carried out. Indonesia emphasizes legal certainty through formal registration, while Singapore prioritizes efficiency and flexibility in trademark registration and dispute resolution mechanisms. Social, economic, and political factors contribute to these differences, where Singapore as a global trade center creates a responsive and adaptive environment to change, while Indonesia focuses more on protecting local industries with a more conservative approach.